Efek Media Sosial Terhadap Kondisi Sosial dan Pola Hidup Sehat Mahasiswa Universitas Negeri Makassar - Satriani, Nur; Alwi, Alimin; Najamuddin, Najamuddin (Indo-MathEdu Intellectuals Journal, 2025)
Students are often exposed to the negative effects of social media, especially if used excessively, which can disrupt sleep, cause anxiety, and even lead to severe depression. This research aims to analyze the impact of social media on the social conditions, lifestyle, and social status of students at Makassar State University. This study employs a qualitative descriptive method with techniques including interviews, observations, and documentation. The subjects of this study are students at Makassar State University who use social media. In this research, the data analysis technique used involves collecting data through interviews with active students from Makassar State University to provide a deeper understanding of the effects of social media usage, as well as documented literature from previous journals and studies obtained from online databases such as Google Scholar, ResearchGate, and PubMed. The results show that social media has a significant effect on social relationships and mental health, as well as the lifestyle of students. This platform facilitates access to information, expands social networks, and motivates individuals to adopt healthier habits. However, the negative effects such as stress, sleep disturbances, and declining physical health cannot be ignored. This issue is exacerbated by the presence of cyberbullying, social comparison, and self-evaluation anxiety that students often experience. Therefore, it is important to use social media cautiously so that the benefits can be enjoyed without detrimental consequences